Voluntary Disclosure and its Impact on the Cost of Capital in Industrial Public Contributing Companies Listed on the Amman Stock Exchange - Alnaimi, Fatin (The Arab Journal of Administration, 2019)
This study aims to demonstrate the impact of the voluntary disclosure on the cost of the capital in the industrial companies listed at the Amman Stock Exchange industrial companies, during the period (2010-2014), the entire population of the study, which consists of (56) companies, was tested To achieve the objectives of this study, the researcher adopted the items of the disclosure used in the study (Abu Fares & Abu Nassar, 2015) and consisting of (41) items of financial and non-financial information, and that companies can disclose Optionally, also have measured the cost of capital, both the cost of Cost of Equity and the Cost of Debt, and the statement of the impact of the voluntary disclosure on each of them, through the analysis of actual financial statements of the industrial companies with Public Contributing Jordanian Companies , and the use of statistical software (SPSS) to analyze these results. The study indicates that the average disclosure in the Jordanian Public Contributing industrial companies rate, is (0.61), which shows how companies perceive the importance of the optional disclosure, also it found the there is the presence of impact, which is statistically significant between the optional disclosure and the cost of capital, with an inverse relationship between the two, and the presence of impact statistically significant between the optional disclosure and Cost of Equity and Cost of Debt, which indicates the role of the optional disclosure in reducing the phenomenon of asymmetry of information between the company and the users of its financial statements, which has led to reduced capital cost of these companies. Researcher recommended, to increase the disclosure of the industrial public ratio, and make use of it to reduce the case of asymmetry of information, which reduces the risk ratio and increases the efficiency of the Amman Financial Exchange, and increases the disclosure of information that meets the needs of the shareholders to guide them in making their investment decisions, and exploit it to achieve its objectives as much as possible to attract investors.